2016
DOI: 10.4081/ejtm.2016.5972
|View full text |Cite
|
Sign up to set email alerts
|

Use it or lose it: tonic activity of slow motoneurons promotes their survival and preferentially increases slow fiber-type groupings in muscles of old lifelong recreational sportsmen

Abstract: Histochemistry, immuno-histochemistry, gel electrophoresis of single muscle fibers and electromyography of aging muscles and nerves suggest that: i) denervation contributes to muscle atrophy, ii) impaired mobility accelerates the process, and iii) lifelong running protects against loss of motor units. Recent corroborating results on the muscle effects of Functional Electrical Stimulation (FES) of aged muscles will be also mentioned, but we will in particular discuss how and why a lifelong increased physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…The authors reported very interesting and exciting data from both rodent and human models that investigated the age-related loss of MNs and the resulting effects on skeletal muscle. We would like to take this opportunity to provide support for the findings reported by Mosole et al 1 by integrating findings we have reported in masters athletes 2-5 and to add to this valuable discussion.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…The authors reported very interesting and exciting data from both rodent and human models that investigated the age-related loss of MNs and the resulting effects on skeletal muscle. We would like to take this opportunity to provide support for the findings reported by Mosole et al 1 by integrating findings we have reported in masters athletes 2-5 and to add to this valuable discussion.…”
mentioning
confidence: 65%
“…We read with great interest a recent article from Mosole et al 1 that synthesized the literature and presented some new data to provide clarity on whether life-long exercise promotes reinnervation of muscle and survival of spinal [motor neurons (MNs)] and [motor units (MUs)] into old age. The authors reported very interesting and exciting data from both rodent and human models that investigated the age-related loss of MNs and the resulting effects on skeletal muscle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 26 , 27 This hypothesis will also be discussed using data from the most recent literature on the specific metabolic-functional muscle markers of CFS comparing them with those derived from sarcopenic muscles. 28-30 …”
mentioning
confidence: 99%
“…Based on present and previous observations changes in absolute and relative number of fiber types, in any experimental model, 246 will ask for morphometry of the whole muscle cross-section, while after muscle sampling only the size of the different types of muscle fibers could be computed. 247 …”
mentioning
confidence: 99%